Dynamical Characteristics Of A Head Expander For Vibration Testing In Pustekbang Laboratory - Nur Mufidatul Ula; Yusuf Giri Wijaya; Muksin Muksin; Mikhael Gilang Pribadi Putra Pratama; Agus Harno Nurdin Syah (Institut Teknologi Dirgantara Adisutjipto, 2020)
Vibration testing of the head expander has been carried out. This test aims to determine the dynamic characteristics of the head expander that used in the Laboratory of Temperature and Vibration Testing, The Aeronautics Technology-LAPAN. The Head expander is used as a testing tool for the needs of large specimens. Validation of the head expander through this experimental method aims to determine the level of homogeneity of the head expanders. Retrieval of data using 4 accelerometers that are placed at each end of the head expanders. Sine sweep vibrations are given from 5 Hz to 2000 Hz with a constant amplitude of 1g and a sweep rate of 1 octave/minute. The test results show that the ends of the head expander have homogeneous properties with natural frequency values that do not differ much. Resonance occurs at a frequency of 900 Hz, 1300 Hz, 1600 Hz and 1900 Hz. The largest amplitude value at 11,76 g occurs at a frequency of 1900 Hz, so this head expander cannot be used for tests above 1900 Hz.